2023
DOI: 10.1002/ejp.2094
|View full text |Cite
|
Sign up to set email alerts
|

Pain paths among post‐COVID‐19 condition subjects: A prospective cross‐sectional study with in‐person evaluation

Abstract: Background: New-onset chronic pain has been acknowledged as part of the post-COVID-19 condition. However, available fine-grained data about its clinical phenotype, trajectories and main associated characteristics remain scarce. We described the distinct temporal evolutions of post-COVID-19 pain and their epidemiological and phenotypical features. Methods: A prospective cross-sectional study enrolled post-COVID-19 condition patients (i.e. who had persisting COVID-19-related symptoms over 30 days since their fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Previous studies indicated that pain associated with long COVID syndrome affects lower limbs or has a widespread distribution in a considerable proportion of patients. 19,30 Three patients had a sars-cov-2 infection more than 3 months before vaccination. Although we cannot exclude that a previous infection may influence generalized sensory symptoms and pain associated with vaccine, these 3 patients had spared QST variables and did not differ from the other patients in clinical variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that pain associated with long COVID syndrome affects lower limbs or has a widespread distribution in a considerable proportion of patients. 19,30 Three patients had a sars-cov-2 infection more than 3 months before vaccination. Although we cannot exclude that a previous infection may influence generalized sensory symptoms and pain associated with vaccine, these 3 patients had spared QST variables and did not differ from the other patients in clinical variables.…”
Section: Discussionmentioning
confidence: 99%
“…68,71 This is also valid for systemic disease, which may affect motor and somatosensory systems in different proportions leading to different types of pain syndromes. 5,63,80,82,101,118 1.2. Pain as a nonmotor symptom of Parkinson disease Motor parkinsonism (also known as akinetic rigid syndrome) is defined by the presence of bradykinesia (ie, the slowness and decrement in amplitude or speed of movement) in combination with rigidity (ie, the increased muscle tonus on slow passive movement of major joints), rest tremor (ie, 4-6 Hz tremor in the fully resting limb, which is frequently suppressed during movement initiation), or both.…”
Section: Recent Advances In the Classification Of Pain Disordersmentioning
confidence: 99%
“…68,71 This is also valid for systemic disease, which may affect motor and somatosensory systems in different proportions leading to different types of pain syndromes. 5,63,80,82,101,118…”
Section: Introductionmentioning
confidence: 99%
“…8,15 In addition, it is notable to remark that studies investigating post-COVID pain but within an overall post-COVID-19 condition have reported lower prevalence rates (10%-20%) than those studies specifically investigating just post-COVID pain (40%-60%). 1,6,17,30,36 It should be also considered that most studies investigating post-COVID pain symptoms have used cross-sectional designs because they assessed the presence of pain just at one follow-up period. 1,6,8,15,17,30,36 Understanding the long-term evolution of post-COVID pain symptomatology may have implications for optimizing patient treatment care, public health outcomes, and for informing patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 In addition, it is notable to remark that studies investigating post-COVID pain but within an overall post-COVID-19 condition have reported lower prevalence rates (10%-20%) than those studies specifically investigating just post-COVID pain (40%-60%). 1,6,17,30,36…”
Section: Introductionmentioning
confidence: 99%